The teaching method in the course "Computer design of technological systems" in Burgas Free University - Dolchinkov, Radostin (Yearbook Telecommunications, 2014)
In modern practice, the role of automation systems design and computer graphics, popular with the name CAD systems (Computer Added Design), are of utmost importance. The rapid penetration of CAD systems in design - mechanical, electronic, and construction - is determined by the following: ï® opportunity to quickly create technical solutions multivariate; ï® using libraries of standard parts and assemblies; ï® manipulation of drawings â€“ connection, sampling; ï® compatibility with other graphic systems.